Boosting the thermoelectric performance of PbSe through dynamic doping and hierarchical phonon scattering. Issue 7 (10th May 2018) - You, Li; Liu, Yefeng; Li, Xin; Nan, Pengfei; Ge, Binghui; Jiang, Ying; Luo, Pengfei; Pan, Shanshan; Pei, Yanzhong; Zhang, Wenqing; Snyder, G. Jeffrey; Yang, Jiong; et al.
Abstract : Cu intercalation is demonstrated to enhance the thermoelectric performance of PbSe through the dynamic doping effect and hierarchical phonon scattering. Abstract : Here we find the peculiar behavior of Cu ions in the PbSe–Cu system increases its thermoelectric performance. For the electrical transport, a dynamic doping effect is achieved because more Cu ions enter into the PbSe lattice and provide extra charge carriers as the temperature increases, which guarantees an optimized carrier concentration over a wide temperature range. For the thermal transport, the presence of Cu2 Se nanoprecipitates and dislocations at a low temperature range as well as the vibration of Cu atoms around the interstitial sites of PbSe at high temperatures result in hierarchical phonon scattering and a significantly reduced lattice thermal conductivity over the whole temperature range. As a result, a peak thermoelectric material figure of merit zT of up to 1.45 and a thermoelectric device figure of merit ZT close to unity are obtained for the sample with 0.375 at% Cu. Furthermore, enhanced thermoelectric properties are also realized for the Cu-intercalated PbS, implying that the temperature-driven dynamic behavior of Cu ions in a rigid lattice can serve as a general strategy to optimize the thermoelectric performance of IV–VI compounds.